Revolutionizing Hepatitis C Treatment: The Cutting-Edge World of Hepatitis C Virus Inhibitors - Haq, Quazi M I; Abbas, Ghulam (PSM Microbiology, 2025)
Hepatitis C Virus (HCV) inhibitors have emerged as a beacon of hope in the battle against a persistent and potentially life-threatening global health threat. This review article delves into the expansive landscape of HCV inhibitors, showcasing their remarkable progress and the transformative impact they have had on the management of HCV infection. The HCV inhibitors can be broadly categorized into three main classes: direct-acting antivirals (DAAs), host-targeting agents, and immunotherapies. DAAs have gained significant attention due to their high efficacy and tolerability. Host-targeting agents, such as cyclophilin inhibitors and microRNA-based therapeutics, present alternative approaches to combat HCV infection by targeting host factors essential for the virus’s life cycle. Immunotherapies, including therapeutic vaccines and monoclonal antibodies, have opened new frontiers in HCV treatment, enhancing viral clearance and reducing the risk of reinfection. Throughout this review, we also address ongoing challenges, including drug resistance, access disparities, and emerging HCV genotypes. As HCV inhibitors continue to evolve, their role in eliminating hepatitis C as a global health threat becomes increasingly prominent. In conclusion, this comprehensive overview of HCV inhibitors underscores their pivotal role in reshaping the landscape of hepatitis C treatment. The ongoing development and diversification of these inhibitors offer optimism for achieving a world free from the burden of HCV infection.